Campanhas de prevenção HIV/AIDS : multimodalidade da linguagem e modelos culturais - Rocha, Sheila da (My University, 2015)
The objective of this dissertation is to analyze and compare the multimodal language from campaigns that prevent HIV/AIDS, mainly focusing in the Cognitive Linguistics perspective by incorporating the approach of regional, cultural and identity factors that are present in the production of these campaigns. In view of that, the guidelines indicated by models of care and public health policies in Brazil were investigated, notably in the case of AIDS. The study also evaluates how social marketing works in an attempt to create better living conditions for all through the use of advertising as a tool to help spreading these concepts. In this research, metaphors and multimodal metonymies, hich appeal to several regions with different characteristics, are brought to light and analyzed. This approach method is used to observe how the advertising language uses these features to provoke reactions of attitudinal and behavioral nature on the target audience. In order to meet this proposition, a corpus was built with the use of eight posters and two billboards of advertising campaigns that were spread in different parts of the country between 2009 and 2015, more than 30 years after the emergence of the epidemic. The study is based on the Conceptual Metaphor Theory proposed by George Lakoff, Mark Johnson and associated authors, as well as in studies of multimodality especially developed by Charles Forceville and other authors cited in the course of the analysis. Through this study is possible to conclude that verbal and visual metaphors/metonymies show regional, cultural and identity traces, bringing together the language of the target audience and highlighting specifics that drive the perceptual process of receivers, which contributes to the effectiveness of the messages that stimulate change of habits and behaviors.
O objetivo desta dissertação é analisar e comparar a linguagem multimodal em campanhas de prevenção HIV/Aids, concentrando-se, principalmente, na perspectiva da Linguística Cognitiva, incorporando a abordagem de fatores regionais, culturais e identitários, implicados na produção dessas campanhas. Para isso, também investigam-se as diretrizes apontadas por modelos de atenção e políticas públicas de saúde no Brasil, em especial ao caso da Aids, e como o marketing social atua na intenção de criar melhores condições de vida para todos, utilizando a publicidade como uma ferramenta de propagação desses conceitos. Nesta pesquisa, são levantadas e analisadas metáforas e metonímias multimodais cujo apelo traz marcas de regionalidades diversas, observando de que forma a linguagem publicitária utiliza esses recursos para provocar reações de natureza atitudinal e comportamental em seu públicoalvo. Para atender a essa proposição, o corpus é formado por oito cartazes e dois outdoors de campanhas publicitárias lançadas em diferentes regiões do país entre 2009 e 2015, passados mais de 30 anos do surgimento da epidemia. A investigação fundamenta-se na Teoria da Metáfora Conceitual, proposta por George Lakoff, Mark Johnson e autores associados, bem como nos estudos sobre multimodalidade, desenvolvidos, especialmente, por Charles Forceville. Através deste estudo, conclui-se que as metáforas/metonímias verbais e visuais evidenciam traços regionais, culturais e identitários, aproximando a linguagem do seu público-alvo e salientando especificidades que acionam o processo perceptivo dos receptores, contribuindo para a eficácia das mensagens que estimulam a mudança de hábitos e comportamentos.
Keywords: Metáfora; Gramática cognitiva; Campanhas publicitárias; AIDS (Doença); Metaphor; Cognitive grammar; Advertising campaigns; Acquired Immune Deficiency Syndrome